A comparison of interferon alfa-2a and podophyllin in the treatment of primary condylomata acuminata. The Condylomata International Collaborative Study Group. (1991)
OBJECTIVES--to compare the response to treatment and recurrence rate of condylomata accuminata using subcutaneous injection of interferon alfa 2a 1.5 million units three times weekly for four weeks, or podophyllin resin 25% applied to lesions twice weekly for up to six weeks. DESIGN--Randomised open study. SETTING--Multicentre European study in genitourinary medicine, dermatovenereology, and gynaecology departments. PATIENTS--87 males and 67 females with condylomata acuminata for less than six months and no history of previous treatment. MAIN OUTCOME MEASURES--Complete clearance of lesions and evidence of recurrence at three months and nine months after treatment commenced. RESULTS--A complete response was achieved at three months in 15 of 64 (23%) in the interferon treated group, and 31 of 69 (45%) in the podophyllin treated group (p = 0.003). At nine months 10 of 13 patients in the interferon group and 22 of 30 patients in the podophyllin group remained completely clear of lesions.